Biological monitoring of workers exposed to engineered nanomaterials - Schulte, P. (Toxicol Lett, 2018)
As the number of nanomaterial workers increase there is need to consider whether biomonitoring of exposure should be used as a routine risk management tool. Currently, no biomonitoring of nanomaterials is mandated by authoritative or regulatory agencies. However, there is a growing knowledge base to support such biomonitoring, but further research is needed as are investigations of priorities for biomonitoring. That research should be focused on validation of biomarkers of exposure and effect. Some biomarkers of effect are generally non-specific. These biomarkers need further interpretation before they should be used. Overall biomonitoring of nanomaterial workers may be important to supplement risk assessment and risk management efforts.